Multifunctional and Photocatalytic Properties of DyFeO₃/Dy₃Fe₅O₁₂ Biphasic Nanoparticles - T. Punitha; P. Balamurugan (International Journal of Crystalline Materials, 2025)
Rare-earth orthoferrites constitute a class of compounds that exhibit remarkable magnetic, optical, and electronic properties across a wide temperature range. In the present study, a dysprosium-based orthoferrite containing dual phases of DyFeO₃ perovskite and Dy₃Fe₅O₁₂ garnet was successfully synthesized via the co-precipitation technique. X-ray diffraction (XRD) analysis was employed to investigate the structural configuration of the synthesized material. The diffraction pattern confirmed the formation of a biphasic composite comprising orthorhombic DyFeO₃ and cubic (bcc) Dy₃Fe₅O₁₂ phases.Field Emission Scanning Electron Microscopy (FE-SEM) was used to examine the surface morphology of the nanoparticles, revealing nearly spherical particles with Crystalline Materials slight agglomeration, thereby providing clear evidence of composite formation. Energy Dispersive X-ray (EDX) spectroscopy further verified the presence of Dy, Fe, and O elements in the sample. The optical band gap, determined from UV–visible absorption spectroscopy using the Tauc plot, was found to be 2.06 eV.Magnetic characterization using a Vibrating Sample Magnetometer (VSM) demonstrated a mixed magnetic behavior—showing a Langevin-type (ferromagnetic) component at low fields and a linear (antiferromagnetic) response at higher fields. Ferroelectric polarization (P–E loop) measurements indicated induced ferroelectric characteristics in the material. Photocatalytic studies under visible light illumination revealed that the DyFeO₃ nanoparticles exhibit an efficient degradation rate of methylene blue (MB) dye, with a progressive decrease in dye concentration over time, confirming the high photocatalytic activity of the synthesized catalyst.
Keywords: Co-precipitation; Dy3Fe5O12; DyFeO3; Electric polarization; Nanocomposite; magnetic property